Which SERVQUAL Dimensions Best Predict Customer Loyalty in High-Contact Service Industries - Elly Joenarni; Eny Rachmawati; Mega Darmi Novita; Ahfi Nova Ashriana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study explores the relationship between service quality dimensions and customer loyalty in high-contact service industries, including healthcare, hospitality, and financial services, particularly in emerging markets. Using the SERVQUAL model, which identifies five key dimensions tangibles, reliability, responsiveness, assurance, and empathy the research examines how these dimensions influence customer loyalty. A quantitative research design is employed, with data collected through a cross-sectional survey of 400 respondents using a structured questionnaire. The study analyzes service quality, customer satisfaction, and loyalty using Structural Equation Modeling (SEM), regression analysis, and Exploratory Factor Analysis (EFA). Findings reveal that reliability and empathy are the most influential factors in fostering loyalty, with customer satisfaction acting as a mediator. Additionally, the research highlights the role of perceived value and customer experience in moderating these effects, particularly in sectors like healthcare and hospitality. The study extends the SERVQUAL model by integrating new dimensions such as customer experience and perceived value, offering a more comprehensive framework for understanding service quality in high-contact industries. These insights provide actionable recommendations for service managers to enhance customer loyalty by addressing both functional and emotional aspects of service quality